CULTURAL ANALYSIS: THE RELATIONSHIP BETWEEN SIGN LANGUAGE SKILLS WITH DEAF SELF-IDENTITY - amin, alimohamad (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
Deaf culture is a significant aspect of social and cultural studies, particularly in relation to the Deaf community as a group with unique identities, values, and cultural practices. In the Deaf community, sign language is not only the primary means of communication but also a critical foundation that shapes both individual and collective identities. Mastery of sign language influences how Deaf individuals understand themselves, interact with their surroundings, and strengthen solidarity within their community. This study focuses on the relationship between sign language proficiency and the development of self-identity among Deaf individuals. The research employs a quantitative approach involving 52 respondents from the Deaf community residing in Jakarta and its surrounding areas. Data was collected using a questionnaire designed to measure sign language proficiency and the self-identity of Deaf individuals. The analysis results indicate a significant positive correlation between the two variables, with a Pearson correlation coefficient value of 0.330 (p < 0.05). These findings suggest that improved sign language proficiency is associated with stronger self-identity among Deaf individuals. This research provides valuable insights into the role of sign language proficiency in shaping self-identity, as well as implications for the development of better educational programs and support for Deaf individuals. This research aims to increase public awareness of the value of sign language, not merely as a communication tool but as an essential component of Deaf culture and identity.